SPEECH FUNCTION OF BEAUTY INFLUENCER HANUM MEGA’S PROMOTIONAL CAPTION IN INSTAGRAM - Emeliya Sukma Dara Damanik; Rora Rizki Wandini (VISION, 2020)
This study aims to discover category of speech function used by a beauty influencer “Hanum Mega’s Promotional Caption in Instagram.  This study refers to Halliday’s Approach as the framework to explain category of speech function coded in instagram caption. This study uses qualitative method. The result shows that Hanum Mega as a beauty influencer dominantly used statement to promote the product.  In small number, Hanum mega also used command and offer in promotional caption. Statement as the dominant type of speech function coded in Hanum Mega’s promotional caption, it also shows that she uses descriptive features to attract her followers buy the products.